Behavior of reinforced concrete slab column connections with various corroded reinforcements under cyclic loading - Yap, Jie Hui (Nanyang Technological University, 2024)
Reinforced concrete is one of the most popular building techniques used in the building structures as it supplies relatively high strength to the concrete and increases the toleration of tensile strain. This enhances the ductility and gives more versatility in design. However, in the past few decades, climate change has brought light upon challenges in the use of reinforced concrete as problems like corrosion arises. Corrosion has always been a problem in reinforced concrete but climate change causes more extreme weather which heightens the speed and level of corrosion. Many previous studies have been focusing on the ultimate shear strength of uncorroded concrete specimens but not corroded specimens. This research conducts experiments on uncorroded and corroded reinforced concrete slab-column connections of Grade 40 to investigate its behavior under seismic loading. The slabs-column connections were casted and corroded according to the specifications mentioned in the report. Only one uncorroded slab and two corroded slabs of different levels of corrosion are tested in this report due to various reasons like time constraints and equipment failure in the Protective Engineering Laboratory. The uncorroded slab acts as a control specimen so that comparison of parameters can be made between corroded and uncorroded slabs. The slab dimensions are 2.1m by 1.175m by 0.15m and the column stump is 0.25m by 0.25m by 0.5m. This report focuses on how the corrosion level impacts the ultimate shear strength and drift ratio of the slab-column connection under seismic loadings.